The implementation of the Islamic communication science–based MBKM curriculum at State Islamic Religious Higher Education Institutions - Prilani; Hakim, Lukman (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2025)
The rapid advancement of information and technology has prompted higher education institutions, particularly State Islamic Religious Universities (PTKINs), to make precise calculations and analyze potential risks when implementing curricula. The Merdeka Belajar Kampus Merdeka (MBKM) policy, introduced by the Ministry of Education, Culture, Research, and Technology, aims to prepare students for the challenges of the workforce through quality education. This study, therefore, aims to analyze the implementation of the MBKM curriculum in Islamic Communication Studies programs at State Islamic Religious Higher Education Institutions (PTKIN), which generally focus on three schemes: Pertukaran Mahasiswa Merdeka (Independent Student Exchange), internships, and research. This study employs a descriptive qualitative approach, collecting data through interviews, observations, and documentation. The study subjects include PTKIN leaders, program coordinators, and students from four selected PTKINs. Despite facing challenges such as differing understandings of the MBKM concept, mismatches between Graduate Learning Outcomes (CPL) and industry needs, and limitations in infrastructure, funding, and human resources, the findings indicate that the MBKM curriculum has been implemented effectively. These findings are expected to provide valuable insights for the future improvement and optimization of the MBKM program. ***** Perkembangan teknologi dan informasi yang pesat mendorong perguruan tinggi, khususnya Perguruan Tinggi Keagamaan Negeri (PTKIN), untuk melakukan perhitungan yang akurat sekaligus menganalisis risiko terburuk yang akan dihadapi dalam implementasi kurikulum. Kebijakan Merdeka Belajar Kampus Merdeka (MBKM) oleh Kementerian Pendidikan, Kebudayaan, Riset dan Teknologi menjadi solusi untuk menyiapkan mahasiswa menghadapi tantangan dunia kerja melalui pembelajaran yang berkualitas. Sehingga, penelitian ini bertujuan untuk menganalisis implementasi kurikulum MBKM pada Program Studi Komunikasi Islam di PTKIN yang rata-rata fokus pada tiga skema, yaitu; Pertukaran Mahasiswa Merdeka, Magang, dan Riset. Metode penelitian menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data melalui wawancara, observasi, serta dokumentasi. Subjek penelitian melibatkan pimpinan PTKIN, pengelola program studi, dan mahasiswa dari empat PTKIN terpilih. Hasil penelitian menunjukan bahwa implementasi kurikulum MBKM berjalan dengan baik, meskipun menghadapi kendala seperti perbedaan pemahaman konsep MBKM, ketidaksesuaian Capaian Pembelajaran Lulusan (CPL) dengan kebutuhan industri, serta keterbatasan sarana prasarana, anggaran, dan sumber daya manusia. Temuan ini diharapkan dapat menjadi masukan dalam memperbaiki dan mengoptimalkan program MBKM di masa depan.